التأويل النحوي في تنبيه الطلبة على معاني الألفية - عبد الفتاح بدرية, نهاد (جامعة الوادي - university of Eloued, 2020)
يعالج هذا البحث قضية من قضايا النحو العربي، ألا وهي قضية التأويل النحوي، حيث يبين لنا مدلول التأويل في اللغة والاصطلاح ومراحل تطوره عند علمائنا الأوائل إلى أن استقر المصطلح في القرن الثامن الهجري، ثم يستقرئ أهم مظاهر التأويل النحوي في كتاب "تنبيه الطلبة على معاني الألفية" لسعيد بن سليمان الكرَّامي السوسي المتوفى سنة (882هـ)، وأهم مظاهر التأويل النحوي، الحذف والاستتار وصوغ المصدر والتقدير في الجمل والمفردات، وتوضيح هذه المظاهر من خلال الشواهد النحوية التي ظهرت فيها قضية التأويل؛ للعودة بتلك الشواهد إلى الجادة التي أرسى علماء العربية قواعدهم عليها. Abstract: This research deals with the issue of Arabic grammar، namely، the issue of interpretation of grammar، where it aims to show the meaning of interpretation in language and terminology and its stages of development by our pioneering scholars until that term had settled in the eighth century AH. The research also extrapolates the most important aspects of interpretation of grammar in the book "Tanbeeh At-talabah ‘ala ma’ani al-alfiyyah” Alerting Students to the Meanings of the Millennium "by Saeed bin Sulaiman Alkarrami Al-Susi died in (882 AH)، and the most important aspects of interpretation of grammar such as deletion، implicitness، and the formulation of the infinitive، and appraisal in sentences and vocabulary، and to clarify all these aspects through the grammatical evidence within which the issue of interpretation emerged. The study then seeks to refer this evidence to the basis on which the Arab scholars laid their rules.
مقال
Keywords: تأويل ، نحو، عربي، تنبيه، معاني الألفية، السوسي; Interpretation, Grammar, Arabic, Alert , Meanings of the alfiya, Al Sosi